Social mobility in Latin America: A review of existing evidence - Viviane Azevedo; César P. Bouillon (Inter-American Development Bank, Research Department, 2009)
This paper reviews evidence on social mobility in Latin America. Several studies have used data sets that collect intergenerational socio economic information. The data, though limited, suggest that social mobility is low in the region, even when compared with low social mobility developed countries like the United States and United Kingdom, with high levels of immobility at the lower and upper tails of the income distribution. While Latin America has improved education mobility in recent decades, which may have translated into higher mobility for younger cohorts, the region still presents, except for Chile, lower education mobility than in developed countries. The paper also reviews studies on the main determinants of the region's low levels of social mobility, including social exclusion, low access to higher education, and labor market discrimination.
Keywords: D30; D60; I30; 330; Social mobility; Latin America; Inequality; Social Exclusion; Education; Soziale Mobilität; Schätzung; Lateinamerika